Pengaruh Jenis Pelarut dan Ultrasonikasi terhadap Ekstrak Fikoeritrin dari Kappaphycus alvarezii : The Effect of Different Solvent Type on Phycoerithryn Extract from Kappaphycus alvarezii - Uju; Anne Mumtaza Putri; Safrina Dyah Hardiningtyas (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2021)
Kappaphycus alvarezii is a type of red seaweed (Rhodophyta) which contains phycobiliprotein pigments. Red seaweed is dominated by phycoerythrin type phycobiliprotein. Phycoerythrin can be obtained from the extraction process. The purpose of this study was to determine the effect of solvent type and acceleration time of ultrasonication extraction on phycoerythrin pigments. The extraction process was carried out in stages using distilled water, CaCl2 and phosphate buffer with ultrasonication acceleration of 35-55 minutes. The results showed that the phycoerythrin pigment extract of K. alvarezii using distilled water produced a more concentrated pigment color than buffer phosphate and CaCl2, showing the highest concentration of 0.057 mg/mL, and a purity index of 0.189. Water solvent is safe to use because water does not have toxic power. So, there is no need to conduct a preliminary test for solvent toxicity. It is more economical than other types of solvents. The extraction of phycoerythrin pigment using distilled water for 45 minutes resulted in a more concentrated pigment color. The concentration of phycoerythrin pigment before and after precipitation was 0.170 mg/mL and 0.421 mg/mL, respectively. The phycoerythrin pigment purity index before and after precipitation was 0.301 and 0.831, respectively. The best antioxidant activity (% inhibition) was found at concentrations of 50 ppm and 80 ppm phycoerythrin pigment with extraction time of 45 minutes at 62% and 89% respectively. Protein profile using SDS-Page showed that phycoerythrin has a molecular weight of 16.27 kDa in the subunit, 17.79 kDa in the subunit β, and 30.60 kDa in the subunit γ.